2012
DOI: 10.1259/dmfr/17113005
|View full text |Cite
|
Sign up to set email alerts
|

Changes of parotid and submandibular glands caused by radiotherapy—an ultrasound evaluation

Abstract: Objective: Radiotherapy may alter the normal morphology of salivary glands located in the radiation field. These changes could be evaluated safely by sonography; however, there have been few studies in this regard. This study is aimed at evaluating the sonographic changes of the parotid and submandibular glands in patients undergoing radiotherapy for head and neck malignancies. Methods: 20 patients (16 males and 4 females) with head and neck malignancies who had been referred for radiotherapy to the Qaem Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 20 publications
(42 reference statements)
5
36
1
Order By: Relevance
“…These features are similar to post-radiotherapy changes in the MSGs (Imanimoghaddam et al 2012;Ying et al 2007) and can be observed in senile MSGs. In addition, no patient exhibited regression of these changes on further follow-up.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These features are similar to post-radiotherapy changes in the MSGs (Imanimoghaddam et al 2012;Ying et al 2007) and can be observed in senile MSGs. In addition, no patient exhibited regression of these changes on further follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…Ultrasonography (US) is the primary imaging modality for pre-and post-operative assessment in PTC patients (Ahuja et al 1995;Kim DW et al 2013;Kim E et al 2008;Kim EK et al 2002). Previous studies (Imanimoghaddam et al 2012;Ying et al 2007) have reported that radiotherapy may change the echotexture, echogenicity and margins of the major salivary glands and may reduce glandular size. To the best of my knowledge, however, no previous study has reported the ultrasonographic features of the MSGs after RIA in PTC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound studies that have demonstrated changes in the sonographic appearance of parotid glands exposed to radiation are mostly qualitative, or at best, semiquantitative (23,24). In addition, previous studies were either on acute toxicity (24) or late toxicity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Xerostomia is one of the most important oral complications of radiotherapy received for the head and neck malignancies and occurs as a result of the damage brought by irradiation of the salivary parenchyma [5,6]. The reduced flow and viscosity of the saliva is a direct result of the damage brought to the radiation sensitive glandular parenchyma and its subsequent reduced salivary gland function [6]. Studies have shown that there are definite links between the exposure of the glands to radiation and the subsequent size reduction [6] and change in the blood flow of the parotid glands [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced flow and viscosity of the saliva is a direct result of the damage brought to the radiation sensitive glandular parenchyma and its subsequent reduced salivary gland function [6]. Studies have shown that there are definite links between the exposure of the glands to radiation and the subsequent size reduction [6] and change in the blood flow of the parotid glands [7]. The parotid gland (PG) function was found to be dose dependent [7,8]; the threshold beyond which the damage to the glandular parenchyma becomes prominent may lay around 30-40 Gy [4].…”
Section: Introductionmentioning
confidence: 99%